Factors influencing the success of live export of South African abalone (Haliotis midae) - Dlamini, Faith Kwanele (Rhodes University, 2026)
South African abalone (Haliotis midae) has been successfully farmed for 35 years, for commercial export to Asian markets. Abalone can either be exported dried, canned, or live, where live export generally fetch a higher price. However, complications arise within the transport phase during export. Abalone experience different negative effects, including a decrease in their survival rate (which ranges from 64 – 97 %) and behavioural response, including failed righting behaviour and a lower speed when locomoting, which indicates increased stress and decreased meat quality. They also experience an increased weight loss, through drip loss, of around 4 – 15% of their total weight, which is costly to farmers as exporters are paid on the landed weight. This research, which was conducted at Aqunion (Pty) Ltd, aimed at improving current farm export practices (Chapter 4) and implementing a pre-cool method (Chapter 3) during the summer months, when increased sea temperatures prevail and further negatively influences the exporting process. This was done by comparing abalone weight, survival, behaviour, and health when subjected to eight different pre-transport conditions, and then subjected to a 42-h transport simulation. These conditions include two different acclimation temperatures, purge days, ice volumes, and for two different animal sizes, which are currently being used on the farm. Pre-cooled tanks were able to achieve a maximum 4-degree Celsius temperature difference from the incoming ambient sea temperature while also maintaining optimal DO and pH concentrations of 8.1 mg/L, 94.5 %, and 8.4, respectively. A higher sludge accumulation was also observed within pre-cooled tanks throughout each purging process. Post transportation, animals were able to retain 170 g more with a longer 3-day purge, and survival was higher by 8 %, 9 %, and 10 % with pre-cooling, longer purge, and a more ice, respectively. Animals were also more responsive in their movement upon arrival by 9 % under a pre-cooled condition and were also able to move at a higher speed of 1.60 ± 0.17 mm s 1. Adhesive force was greater for both big and small animals by 1.93 N and 0.70 N when transported with more ice. Results from this research give further insight into the current recommendations for pre-transport exporting procedures, during standard export environmental conditions and during summer conditions. This, in turn, will lead to reduced losses during export and an increase in annual revenue for abalone producers.
Keywords: Aquaculture industry (http://id.loc.gov/authorities/subjects/sh85006214); Haliotis midae (http://id.loc.gov/authorities/subjects/sh2006004361); Haliotis midae fisheries (http://id.loc.gov/authorities/subjects/sh2010015291); Live export (https://www.wikidata.org/wiki/Q6657142)